Erratum: Yang, Y.C., Yin, Z.W. & Yu, W.D. (2012) A new species of Tyrinasius Kurbatov (Coleoptera, Staphylinidae, Pselaphinae) from Ningxia, Northwest China. Zootaxa, 3401, 60–62. - Yang, Y. C.; Yin, Z. W.; Yu, W. D. (Zootaxa, 2012)
(Erratum)